Syndromes, Disorders and Maternal Risk Factors Associated with Neural Tube Defects (IV) - Chih-Ping Chen (Elsevier, 2008)
Fetuses with neural tube defects (NTDs) may be associated with maternal and fetal risk factors. This article provides a comprehensive review of maternal and fetal risk factors associated with NTDs, such as infertility, periconceptional clomiphene use and assisted reproductive technology, periconceptional folic acid deficiency and effects offolic acid supplementation and fortification on NTD rates, periconceptional vitamin B1 2 deficiency, single nucleotide polymorphisms and polymorphisms in genes of folate metabolism, and maternal autoantibodies to folate receptors. NTDs associated with maternal and fetal risk factors are an important cause of NTDs. Perinatal identification of NTDs should alert the clinician to the maternal and fetal risk factors associated with NTDs, and prompt a thorough etiologic investigation and genetic counseling. [Taiwan J Obstet Cynecol 2008;47(2):141-1 50]